Tożsamość hybrydyczna jako próba przezwyciężenia dylematów epoki końca wzorców - Szymanowska, Joanna (Er(r)go. Teoria - Literatura - Kultura, 2004)
The article presents the works of an Italian writer, Alberto Savinio as an original model of literature “beyond clear-cut distinctions”. Drawing from the theories of Roland Barthes and Jacques Derrida, it demonstrates to what extent this particular model, based on a conscious deconstruction of both formal and conceptual structure of discourse, leads to the overthrow of a cultural stereotype due to a new reading of the opposition me/other, open/ closed, familiar/strange, known/unknown etc. To achieve that goal Savinio uses the titular “hybrid identities” and the strategy of hybridization of the depicted reality. Savinio, for a long time excluded from mainstream criticism, appears to be a very contemporary writer and his reinterpretation of conceptual basis of the Western culture turn him into a postmodernist author avant la lettre.